Varstrometry for Off-nucleus and Dual Subkiloparsec AGN (VODKA). SDSS J1608+2716: A Subarcsecond Quadruply Lensed Quasar at z = 2.575 - Li, Junyao; Liu, Xin; Shen, Yue; Oguri, Masamune; Gross, Arran C.; Zakamska, Nadia L.; Chen, Yu-Ching; Hwang, Hsiang-Chih (Astrophysical journal. Letters, 2023)
We report Hubble Space Telescope (HST) Wide Field Camera 3 deep IR (F160W) imaging of SDSS J1608+2716. This system, located at a redshift of z = 2.575, was recently reported as a triple-quasar candidate with subarcsecond separations (∼0.″25) based on selection from Gaia astrometry and follow-up Keck adaptive optics–assisted integral field unit spectroscopy. Our new HST deep IR imaging reveals the presence of a fourth point-like component located ∼0.″9 away from the triple system. Additionally, we detect an edge-on disk galaxy located in between the four point sources. The entire system exhibits a characteristic cusp structure in the context of strong gravitational lensing, and the observed image configuration can be successfully reproduced using a lens model based on a singular isothermal ellipsoid mass profile. These findings indicate that this system is a quadruply lensed quasar. Our results highlight the challenges associated with identifying dual/multiple quasars on ∼kiloparsec scales at high redshifts and emphasize the crucial role of deep, high-resolution IR imaging in robustly confirming such systems.